Indirect Expropriations in Investment As a Result of the Exercise of the Regulatory Power and its Relationship with the Patrimonial state Liability of the Public Administration - Terrazos Poves, Juana Rosa (2014)
In this article the authors highlight the promotion of private sector participation in infrastructure development for the provision of public services, through joint actiondesigned for the private and public sector instruments. Under that context, they take asa starting point the figure of corporate governance, as an efficient state action, because itinvolves a change in the conception of the state and non-state roles in investment in publicservices, considering the actors public and private, as a cooperating conjunction with theformulation and implementation of public policies.In this context, the authors develop and analyze pending tasks in the exercise of regulatoryauthority and its relation to the patrimonial liability of the State, which in their view must also be taken into account for the effectiveness of corporate governance.